Optimization of Early Childhood Social Emotional Development Through Exercise Methods and Learning Videos - Raisa Nur Salum; Khadijah Khadijah; Nurul Liza Nasution (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This research aims to investigate ways to enhance the social and emotional development of young children through Drill and video learning methods. The research topic covers the definition and importance of social-emotional development in young children, learning through Drill and video methods in young children, and strategies to enhance social-emotional development through Drill and video methods in young children. The method used in this research is qualitative with a literature study, using data sources such as journals and books published in the last 5 years. The results show that, first, social-emotional development in young children refers to the process by which children develop the ability to interact socially and manage their emotions effectively. This involves understanding and expressing emotions, developing social relationships, and adapting to their social environment. Second, learning through Drill and video methods is an effective way to encourage active participation, cooperation, and the development of social-emotional skills in young children. Through Drill and video learning methods, children can learn to interact, share, and collaborate while also developing cognitive and academic skills. Third, strategies to optimize the social-emotional development of young children through Drill and video learning methods include forming inclusive groups, facilitating positive interactions, developing social skills, cooperative games, facilitating emotional expression, positive feedback, and leadership concept building.